2004
DOI: 10.1097/01.cmr.0000129374.76399.19
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nuclear factor-κB and nitric oxide by curcumin induces G2/M cell cycle arrest and apoptosis in human melanoma cells

Abstract: Curcumin (diferuloylmethane) inhibits tumour cell growth by inducing apoptosis in many tumour types, including melanoma, via complex and ill-defined pathways. Recent studies have shown that curcumin is both a nitric oxide scavenger and an inhibitor of inducible nitric oxide synthase (iNOS) expression, low levels of which correlate with antiapoptotic function and poor survival and which may be regulated by inhibition of nuclear factor-kappaB (NFkappaB) activation. To elucidate the mechanisms by which curcumin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 29 publications
10
84
0
Order By: Relevance
“…Zheng et al also reported that curcumin induced a G 2 -M block followed by apoptosis in melanoma cells, and this was associated with p53 and p21 up-regulation (39). p27 was also more prominent in Bcr-Abl-expressing cells after 18 hours of curcumin treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Zheng et al also reported that curcumin induced a G 2 -M block followed by apoptosis in melanoma cells, and this was associated with p53 and p21 up-regulation (39). p27 was also more prominent in Bcr-Abl-expressing cells after 18 hours of curcumin treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Another study showed that curcumin suppresses constitutively active NF-nB in multiple myeloma and mantle cell lymphoma (21,22). Curcumin has also been shown to arrest cell growth at the G 2 -M phase and induce apoptosis in human melanoma cells by inhibiting NF-nB activation (23). The role of curcumin in Burkitt's lymphoma has been not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…NO release induces antiapoptotic effects, prolonging the survival of melanoma cells in vitro. [9][10][11] Data from our laboratory and from others reported iNOS expression in the vast majority of melanoma tissue specimens and cultured melanoma cells, 6,[12][13][14][15][16] suggesting a role for iNOS in the development and progression of cutaneous melanoma. However, to our knowledge, no study has investigated the expression of iNOS in relation to angiogenesis of lymphatic and blood vessels in melanocytic lesions.…”
mentioning
confidence: 99%